Long-term outcomes from critical care. Issue 1 (January 2021) - Morgan, Amy
Abstract: With the improved survival of critical care patients, a cohort of chronically critically ill patients has emerged. These patients have a higher 5-year morbidity and mortality and greater utilization of healthcare resources. This well-documented deterioration in physical, cognitive and/or psychological health in critical care survivors is known as post intensive care syndrome (PICS) which has personal and socioeconomic implications not only for the patient, but also for their families, care givers and society. Greater awareness of the impact of critical illness on quality of life has led to the emergence of research focused on overall patient outcomes rather than crude survival. National guidelines state personal rehabilitation programmes involving a multidisciplinary team should be commenced within 4 days of admission and continued after discharge to the ward. Once discharged home specialist ICU follow-up clinics are key in identifying any long-term complications of critical care admission and should focus on all aspects of the PICS. COVID-19 has highlighted PICS on a national level with patients experiencing multiple long-term complications of critical illness, some as yet unknown.